Trastorno del espectro autista e inteligencia en un estudiante - Merino Zurita, Jessica Lorena (2020)
This case study has as its theme: Autism spectrum and intelligence disorder in a student of the Maria Auxiliadora Private Basic Education Institution, and as a goal the relationship between these two variables, thus determining the diagnostic criteria, the IQ and establishing the intervention individual, family and academic psychotherapeutic. We used techniques such as the observation sheet, medical history, psychometric techniques such as tests of the M-CHAT test, family APGAR, non-verbal Wechsler scale. The analysis of these allows to confirm that the student presents diagnostic criteria of ASD, and there is no relationship with intelligence. The affected areas are: cognitive, affective, social-behavioral, so the psychotherapeutic intervention was carried out with the Cognitive-Behavioral model with the applied Behavioral Analysis (ABA) approach.